5‐ALA in the management of malignant glioma. Issue 5 (8th May 2018) - Stepp, Herbert; Stummer, Walter
Abstract : Background: Patients suffering from malignant gliomas have a poor prognosis. For the surgical treatment of these tumors, 5‐aminolevulinic acid (5‐ALA) has become a new standard. Aims: This review intends to provide an overview over current status, significance, limitations, and future perspectives of 5‐ALA based fluorescence guided surgery and photodynamic therapy for brain tumor patients. Materials and Methods: From peer reviewed publications on the many aspects connected with this topic, those with potential clinical relevance were selected and put in the context of our own experience. Results and Discussion: The high tumor selectivity of accumulation of fluorescent protoporphyrin IX (PpIX) after systemic administration of 5‐ALA enables intra‐operative fluorescence guidance, which is unimpaired by brainshift and does not require expensive equipment. The neurosurgical aim of complete resection of enhancing tumor can now more easily be achieved, which improves prognosis in these patients. Nevertheless, despite better surgery tumors will inevitably recur. In order to further prolong survival, the phototoxic properties of PpIX are presently being exploited in clinical trials of post‐operative or interstitial photodynamic therapy (PDT). Conclusion: 5‐ALA based fluorescence guidance and PDT offer an intriguing new option for the management of malignant gliomas. Lasers Surg. Med. 50:399–419, 2018. © 2018 The Authors. Lasers in Surgery and Medicine Published by Wiley Periodicals LLC